Análise molecular do polimorfismo do gene da enzima óxido nítrico sintase endotelial na endometriose - Silva, Rita de Cássia Pereira da Costa e (2017)
Endometriosis is defined by the emergence of foci of endometrial tissue with glandular and stromal or characteristics identical to those of the uterine cavity in other locations than the endometrium and focuses primarily on women of reproductive age. It is present in 10% of the general population and in 50% of cases of infertility, showing a strong genetic component by correlating the disease with various polymorphisms. One of them, G894T of eNOS gene of the enzyme endothelial nitric oxide synthase (eNOS) has been studied by have implications with infertility. The present study examined the allele frequency and genotype of this polymorphism in women with endometriosis storied in fertile and infertile. Blood samples were used 47 women with endometriosis from a center of reference in laparoscopy and infertility of the city of Goiânia, Goiás. The DNA was extracted and measured for genotypic analysis (PCR/RFLP) with primers and controls to enlarge the gene eNOS G894T. In the statistical analysis we used the Chi square tests and/or Fisher and Mann-Whitney. The patients had an average age 32.5 ± 2.9 years. Was demonstrated difference in average age between fertile and infertile patients p = 0.034, fertile was demonstrated 39,9± 3,0 anos, and infertile 37,3 ± 5,6 anos. Genotype polymorphism frequencies in study were: GG 59.6% 29.8% and GT TT 10.6%; to split into sub-groups of fertile and infertile met respectively: 70% and 50% GG; GT 30% and 29.2%; TT was null between fertile and infertile 20.8%. The allele frequency between the fertile and infertile, was, respectively: G 85% and 15% T; G 64.6% and 35.4% T, p = 0.04 (95% CI 3.0 OR = 1.12-8.29). In the frequency analysis of genotypic heritage models, codominant and recessive were respectively: (GG vs. TT) 59.6% (28/47) vs. 10.6% (5/47) p = 0.044 and recessive (TT vs. GT + GG) was 10.6% (5/47) vs. 89.4% (42%) p = 0.049. The study showed that the presence of the T allele of eNOS gene G894T polymorphism of endothelial nitric oxide synthase enzyme in fertile and infertile patients have an important role in the increase of endometriosis and in homozygous T allele confers risk for the infertility in endometriosis in women in the city of Goiânia-Goiás.